Multi-lattice inner structures for high-strength and light-weight in metal selective laser melting process - Dongseok Kang; Sanghu Park; Yong Son; Simo Yeon; Sang Hoon Kim; Ilyong Kim (Materials & Design, 2019)
Due to the development of additive manufacturing (AM), lattice structure which cannot be fabricated by the conventional manufacturing process or have shape restriction has attracted much attention. We propose a new lightweight design method using two types of lattice structures considering the manufacturability in the metal selective laser melting (SLM) and structural characteristics. Firstly, the specific procedure for the proposed design method is presented. In order to apply the two lattice structures, relative density criterion is derived by fabricating experiments using metal SLM process and analyzing geometry according to relative density. The optimal relative density distribution is calculated by performing the topology optimization with minimum relative density using a commercial software package. This proposed method is computationally and experimentally validated by a three-point bending test. Simultaneously, the same procedure is applied to uniform lattice for comparison with the proposed method. This proposed design has a 46% increase in stiffness, a relative flexural rigidity of 35% compared to the solid material, and has a deformation mode different from the uniform lattice. This design sets the standard for using two lattice structures and gives a new perspective on lightweight design with lattice structures. Keywords: Lattice structure, Lightweight design, Additive manufacturing, Topology optimization, Selective laser melting (SLM), Sandwich panel